2021
DOI: 10.3390/ijms23010151
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clear Cell Papillary Renal Cell Carcinoma (ccpRCC)

Abstract: Renal cell carcinomas (RCCs) is a group of various malignant tumours of the renal cortex displaying distinct clinical, morphologic, and genetic features. Clear cell papillary renal cell carcinoma (ccpRCC), belonging to this group, shares morphologic features with both clear cell renal cell carcinoma (ccRCC) and papillary renal cell carcinoma (pRCC) and therefore, more strict diagnostic criteria should be developed to avoid misdiagnosis. Despite overlapping features, ccpRCC has also distinct clinical behaviour,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Another limiting factor for our case report is the lack of a multi-omics approach, specifically, transcriptome sequencing, epigenome sequencing, and non-coding RNA sequencing. These NGS methods would offer invaluable insights into the progression of low-grade, non-invasive PRCC to high-grade, frank-invasive PRCC, and the surrounding normal tissue molecular portrait in association with these neoplasms [ 18 ]. This testing methodology could be employed to offer better tumorigenesis and tumor progression biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Another limiting factor for our case report is the lack of a multi-omics approach, specifically, transcriptome sequencing, epigenome sequencing, and non-coding RNA sequencing. These NGS methods would offer invaluable insights into the progression of low-grade, non-invasive PRCC to high-grade, frank-invasive PRCC, and the surrounding normal tissue molecular portrait in association with these neoplasms [ 18 ]. This testing methodology could be employed to offer better tumorigenesis and tumor progression biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…ccpRCC has different morphologic and immunohistochemical features, but it does overlap with other entities, such as papillary RCC and clear cell RCC. Some of the unique immunohistochemical features of this tumor are the robust diffuse positivity for cytokeratin (CK)7 and cup-like staining for carbonic anhydrase IX (CA9) of its cells [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Up to 80% of kidney tumors are renal cell carcinomas (RCCs); The most common type of RCC is clear cell renal cell carcinoma (ccRCC), occupying approximately 75% of all cases, followed by papillary renal cell carcinoma (pRCC) [ 1 , 2 ]. It has been reported that for 70% of patients with localized pRCC, the overall survival was 5 years, while with advanced pRCC, no treatment options were available [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%